Ketahanan Pangan di Kampung Adat dan Non-Kampung Adat - Perdanaputra, Fauzi; Prasodjo, Nuraini Wahyuning (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2018)
The aims of this research are to analyze the differences of local wisdom and food security household in an indigenous village and non-indigenous village and to analyze the correlation between local wisdom and food security. Research respondents are housewives or housewives who also act as head of household. The research method used a quantitative approach with questionnaire instruments supported by qualitative data with in-depth interview. The results show that there are the difference of food security in Ciptagelar Village and Tonjong II Village which the level of household local wisdom and food security in Kampung Ciptagelar is higher than in Kampung Tonjong II. In addition, from the three dimensions of local wisdom tested, there are two dimensions that have a positive and quite strong relationship with food security, that is the dimensions of local knowledge and community solidarity and compliance with rules and leaders.Keywords: Food Security, Indigenous Village, Local Wisdom, Non-Indigenouse VillageABSTRAKPenelitian ini bertujuan untuk menganalisis perbedaan kearifan lokal dan ketahanan pangan rumah tangga di Kampung adat dan non-kampung adat serta menganalisis hubungan antara kearifan lokal dengan ketahanan pangan. Responden penelitian merupakan ibu rumah tangga atau ibu rumah tangga yang juga berperan sebagai kepala rumah tangga. Metode penelitian menggunakan pendekatan kuantitatif dengan instrumen kuesioner yang didukung dengan data kualitatif dengan metode wawancara mendalam. Hasil penelitian menunjukkan bahwa terdapat perbedaan tingkat ketahanan pangan di Kampung Ciptagelar dan Kampung Tonjong II yang mana tingkat kearifan lokal dan tingkat ketahanan pangan rumah tangga di Kampung Ciptagelar lebih tinggi dibandingkan dengan Kampung Tonjong II. Selain itu, dari tiga dimensi kearifan lokal yang diuji, terdapat dua dimensi yang memiliki hubungan positif dan cukup kuat dengan ketahanan pangan yakni dimensi pengetahuan lokal dan solidaritas masyarakat dan kepatuhan pada aturan serta pemimpin.Â Kata kunci: Kampung Adat, Kearifan Lokal, Ketahanan Pangan, Non-kampung Adat